(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The present study aimed to examine the effects of applied Thai traditional massage combined with knee exercise on knee osteoarthritis (OA) patients. To achieve the research objective, a randomized controlled trial was conducted. The data were collected from 31 knee OA patients using a survey questionnaire, a 10-level pain intensity assessment scale, the Western Ontario and McMaster Universities Osteoarthritis Index, and the Thai version of the Oxford Knee Score translated by the Royal College of Orthopaedic Surgeons of Thailand. Then the data were analyzed using descriptive statistics and the paired sample t-test. The results showed that the majority of the subjects were female aged 60 or over. After the administration of the treatment, almost three-fourths reported experiencing less severe OA and lower knee pain. Also, a pre- and post-treatment comparison revealed increased knee range of extension and flexion measured with a goniometer and improved quality of life at the significance level of 0.05. Based on the findings, it can be concluded that applied Thai traditional massage combined with knee exercise can effectively alleviate OA by relieving muscle contraction, enhancing blood circulation, and strengthening the knee joint.